Moderating Knowledge on Planned Behaviour Theory Toward Intention of Using Islamic Financial Services - Anna Sardiana (Li Falah: Jurnal Studi Ekonomi dan Bisnis Islam, 2021)
The study aims to examine students' behavior described through the theory of planned behavior (TPB) to use Islamic financial services by moderating knowledge. Primary data was used with 350 samples of a random population. Data were analyzed using Smart PLS assistance. The results of this study indicate that there is a significant influence on attitude has a positive relationship, but it does not have a significant effect on the intention to use Islamic financial services. The subjective norms and perceived behavioral control positively influence a positive relationship to use Islamic financial services. As for moderating the choice to use Islamic financial services on the personal norm variable, it has a negative direction but has a significant effect. Perceived behavioral control variable has a positive relationship and significantly impacts using Islamic financial services with the moderation of knowledge. Meanwhile, attitudes moderating knowledge do not significantly affect the intention to use Islamic financial services but have a positive direction.